Penerapan Metode Learning by Doing Untuk Meningkatkan Keterampilan dan Kepercayaan Diri Peserta Kursus Dalam Berwirausaha LKP DINA Depok - Soffiatun, Soffi; Al Faruq, Ubaid; Rahman Hakim, Dani (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2026)
This Community Service (PKM) project aims to implement the findings of a research study titled "The Impact of Accreditation in Improving the Management Quality of the DINA Vocational Training Center (LPK) Depok." One of the key findings indicated that while the quality of graduates is already commendable, there is a significant lack of interest in entrepreneurship. This condition is inconsistent with the objectives of government-funded training grants provided through the Department of Education and Culture. Independent entrepreneurship is the primary target of the Beauty Cosmetology training at LKP DINA, which is designed to foster independent family economic welfare. Theoretical studies suggest that one way to enhance skills and self-confidence in learning is by applying the "learning by doing" method—a learning approach characterized by direct demonstration and practice. The objective of this PKM is to improve the entrepreneurial skills and self-confidence of LKP DINA Depok participants through the implementation of the "learning by doing" method. The program targets 20 participants, with the goal of increasing their competence and confidence to pursue independent entrepreneurship. The intended output of this project is a scientific publication in a community service journal. Keywords: learning by doing, skills, self-confidence, entrepreneurship